Standardization of chrysanthemum cv. Mother Teresa to different potting media under Tarai field conditions (Indian Journal of Arid Horticulture, 2025)
A study on response of pot mum cv. Mother Teresa to different potting media under open field conditions was conducted during 2009-10 at GBPUA&T, Pantnagar. In the present investigation, eight growing media were tested. Plants growing in plastic pots containing cocopeat+sand + FYM+vermicompost (2:1:0.5:0.5) media exhibited the maximum plant height (36.00 cm), and number of primary and secondary branches (3.67 & 17.67, respectively). Number of flowers per plant (34.0) was recorded maximum in cocopeat + sand+vermicompost (2:1:1). Plants took minimum days for flowering (57.00) when grown in cocopeat + sand+ FYM. Flower diameter was observed maximum (5.73 cm) in plants grown in cocopeat + sand +FYM + vermicompost. Maximum duration of flowering (28.13 days) was observed in growing media namely cocopeat+sand+vermicompost. Keeping in view the response of chrysanthemum cv. Mother Teresa to different growing media containing cocopeat + sand + FYM + vermicompost (2:1:0.5:0.5) can be recommended for quality pot mum production under open conditions.
Keywords: Pot mum; growing media; open field; vegetative; floral traits